2006
DOI: 10.1021/jo0615302
|View full text |Cite
|
Sign up to set email alerts
|

Using Kamlet−Taft Solvent Descriptors To Explain the Reactivity of Anionic Nucleophiles in Ionic Liquids

Abstract: In this paper, we report the effect of ionic liquids on substitution reactions using a variety of anionic nucleophiles. We have combined new studies of the reactivity of polyatomic anions, acetate, trifuoroacetate, cyanide, and thiocyanide, with our previous studies of the halides in [C4C1py][Tf2N], [C4C1py][TfO], and [C4C1im][Tf2N] (where [C4C1im]+ is 1-butyl-3-methylimidazolium and [C4C1py]+ is 1-butyl-1-methylpyrrolidinium) and compared their reactivities, k2, to the same reactions in the molecular solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
118
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 47 publications
(35 reference statements)
3
118
0
Order By: Relevance
“…13,15,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][47][48][49][50][51] It should be highlighted that the hydrogen-bond acceptor strength of an IL is dominated by its anion while the hydrogen-bond donor ability is essentially controlled by the cation and only slightly depends upon the anion of the IL. 18,19 Thus, and since we were focused on developing an extended series for the hydrogen-bond acidity of ILs, ILs comprising a fixed anion ([NTf 2 ] − ) and a wide range of cations (imidazolium-, pyridinium-, piperidinium-, pyrrolidinium-, ammonium-, sulfonium-, and phosphonium-based) were selected.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][47][48][49][50][51] It should be highlighted that the hydrogen-bond acceptor strength of an IL is dominated by its anion while the hydrogen-bond donor ability is essentially controlled by the cation and only slightly depends upon the anion of the IL. 18,19 Thus, and since we were focused on developing an extended series for the hydrogen-bond acidity of ILs, ILs comprising a fixed anion ([NTf 2 ] − ) and a wide range of cations (imidazolium-, pyridinium-, piperidinium-, pyrrolidinium-, ammonium-, sulfonium-, and phosphonium-based) were selected.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of efforts to detect such a phenomenon, detailed quantitative investigations on the effects of ionic liquids on reactions of solutes have repeatedly demonstrated that the results can be correlated with, and hence rationalized in terms of, polarity behaviours originally derived to describe molecular solvents. 4,5 In particular, we have previously reported quantitative kinetic studies of nucleophilic substitutions by halides in reactions with neutral nucleophiles in a range of ionic liquids, showing that both cation and anion variation can change the nucleophilicity of the halide ion. 4 By comparing the kinetic data obtained against empirical solvent polarity measurements, 4 it became apparent that this could be understood by the application of the classical Hughes-Ingold predictions 4 of solvent polarity on reaction rates combined with an analysis of hydrogen-bonding effects, with the ionic liquid acting in the same way as polar molecular solvents.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent estimations, the number of potential anion-cation combinations available equates to around one trillion (10 12 ) different ILs. 1 Their proposed applications include recyclable solvents 2,3 , molecular solvent replacements for catalysis, 4 electrochemistry, 5 synthesis 6 and elemental analysis 7 . Past reviews have provided detailed insight into the synthesis and properties of ILs and have promoted their implementation as common laboratory solvents.…”
Section: Introductionmentioning
confidence: 99%